Will/Heart/Spirit: Discipleship that Forms the Christian Character - Porter, Steven L. (Christian education journal, 2019)
This article seeks to provide some clarity on the role of human will in Christian formation through engaging Dallas Willard's understanding of the human will/heart/spirit. The first part of the article examines the value of coming to have an accurate understanding of the role and formation of the will. Section two investigates the Gospel writers' portrayal of Jesus' will in his incarnate life on earth. And the third section draws off Willard's views in order to further develop our understanding of the role of the human will in spiritual formation as well as the formation of the will itself.